2018
DOI: 10.1136/archdischild-2017-314559
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric outcomes and timing of admission

Abstract: Studies of adult patients have demonstrated that weekend admissions compared with weekday admissions had a significantly higher hospital mortality rate. We have reviewed the literature to determine if the timing of admission, for example, weekend or weekday, influenced mortality and morbidity in children. Seventeen studies reported the effect of timing of admission on mortality, and only four studies demonstrated an increase in those admitted at the weekend. Meta-analysis of the results of 15 of the studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Variables associated with healthcare processes, such as the time of day of the test, can therefore provide additional insight into the patient’s health, which can improve the accuracy of predictive models. Some widely investigated healthcare processes, including the timing of hospital admission, surgical procedures on weekends and handover during anaesthesia, have been shown to be associated with clinical outcomes 1–4. More recently, healthcare processes of the laboratory tests, such as the hour of day for ordering a test, day of the week and period since the last test, have been investigated in the hospitalised patients, and the results showed that these healthcare process variables were associated with the survival outcome, independent of their pathophysiology values 5.…”
Section: Introductionmentioning
confidence: 99%
“…Variables associated with healthcare processes, such as the time of day of the test, can therefore provide additional insight into the patient’s health, which can improve the accuracy of predictive models. Some widely investigated healthcare processes, including the timing of hospital admission, surgical procedures on weekends and handover during anaesthesia, have been shown to be associated with clinical outcomes 1–4. More recently, healthcare processes of the laboratory tests, such as the hour of day for ordering a test, day of the week and period since the last test, have been investigated in the hospitalised patients, and the results showed that these healthcare process variables were associated with the survival outcome, independent of their pathophysiology values 5.…”
Section: Introductionmentioning
confidence: 99%
“…An important point which was not discussed by Ramsden et al 1 is that the population of children admitted over the weekend is skewed towards the sicker end of the disease severity spectrum in comparison with children admitted on Mondays to Fridays, and this may explain some of the apparently ‘poorer’ outcomes after a weekend admission. While fewer children are admitted per day on Saturdays and Sundays, there is a 20% increase in admission with asthma and diabetes compared with weekdays,2 and the absolute number requiring high dependency and intensive care is constant 7 days a week 2.…”
mentioning
confidence: 97%
“…The findings of Ramsden et al ’s review1 are replicated in our study of all admissions to hospitals in Scotland in 2000–2013 2. Our study was published too late for inclusion in the Ramsden  et al ’s review,1 but also found no evidence of increased mortality after a weekend admission, and we did find evidence of longer duration of admission in the form of a 7% reduction in zero day admissions over weekends compared with weekdays2 (ie, where a child is admitted and discharged home on the same day).…”
mentioning
confidence: 99%
See 2 more Smart Citations